Mild Deficits of Cortical Bone in Young Adults With Klinefelter Syndrome or Anorchia Treated With Testosterone - Wong, Sze Choong; Scott, David; Lim, Angelina; Tandon, Smriti; Ebeling, Peter R.; Zacharin, Margaret (The journal of clinical endocrinology and metabolism, 2015)
Context:There are currently no data evaluating volumetric bone mineral density (BMD), bone geometry, and body composition in adults with Klinefelter syndrome (KS) or anorchia who have been treated with T from adolescence.Objective:To determine volumetric BMD, bone geometry using peripheral quantitative computed tomography (pQCT), and body composition using dual-energy x-ray absorptiometry (DXA) in men with classical KS or anorchia treated with T from adolescence (age, <16 y), compared with matched controls.Methods:Twenty subjects (12 KS, eight anorchia) and 20 controls underwent a pQCT (66% tibia, 4% radius) and total body DXA.Results:Using adjusted regression models, there was reduced tibial cortical area (95% confidence interval [CI], −88.8 to −4.4 mm2; P = .03) and thickness (95% CI, −0.98 to −0.10 mm; P = .02) in subjects. All other bone parameters were similar between groups. Subjects had significantly higher fat mass (95% CI, 1.6 to 14.9 kg; P = .02), trunk:leg fat ratio (95% CI, 0.09 to 0.60; P = .01), and visceral adipose mass (95% CI, 0.057 to 0.283 kg; P = .004). Lean mass was similar in both groups. Lean mass was positively associated with tibial cortical area and radial total, trabecular, and volumetric density (P < .05).Conclusion:This first report using pQCT and DXA in men with KS or anorchia treated from adolescence showed normal volumetric BMD but reduction in cortical area and thickness, only at the 66% tibia site. Our study also demonstrated for the first time that men with KS or anorchia have increased visceral adiposity despite T treatment.